Thermo-electrochemical production of compressed hydrogen from methane with near-zero energy loss. Issue 12 (December 2017) - Malerød-Fjeld, Harald; Clark, Daniel; Yuste-Tirados, Irene; Zanón, Raquel; Catalán-Martinez, David; Beeaff, Dustin; Morejudo, Selene; Vestre, Per; Norby, Truls; Haugsrud, Reidar; Serra, José; Kjølseth, Christian
Abstract Conventional production of hydrogen requires large industrial plants to minimize energy losses and capital costs associated with steam reforming, water–gas shift, product separation and compression. Here we present a protonic membrane reformer (PMR) that produces high-purity hydrogen from steam methane reforming in a single-stage process with near-zero energy loss. We use a BaZrO3 -based proton-conducting electrolyte deposited as a dense film on a porous Ni composite electrode with dual function as a reforming catalyst. At 800 °C, we achieve full methane conversion by removing 99% of the formed hydrogen, which is simultaneously compressed electrochemically up to 50 bar. A thermally balanced operation regime is achieved by coupling several thermo-chemical processes. Modelling of a small-scale (10 kg H2 day−1 ) hydrogen plant reveals an overall energy efficiency of >87%. The results suggest that future declining electricity prices could make PMRs a competitive alternative for industrial-scale hydrogen plants integrating CO2 capture. Hydrogen is mainly produced industrially via steam methane reforming, a multistage process carried out in large plants to minimize energy losses and costs. Here, by exploiting thermal integration in a protonic membrane reformer, the authors produce compressed hydrogen in a single step with high efficiency.